Marriages, Families, and Relationships: Making Choices in a Diverse Society, 14th Edition - Mary Ann Lamanna; Agnes Riedmann; Susan D Stewart (Cengage Learning, 2020)
Lamanna/Riedmann/Stewart's bestselling MARRIAGES, FAMILIES, AND RELATIONSHIPS: MAKING CHOICES IN A DIVERSE SOCIETY, 14th edition, combines a rigorous scholarly and applied approach with a theme especially relevant to today's dynamic global environment: making choices in a diverse society. Thoroughly revised and updated with the latest data and research, the text delivers an engaging narrative that offers insightful perspectives on the diversity of our modern society, including different ethnic traditions and family forms. The balanced presentation discusses a variety of theoretical perspectives, emphasizing both social structure and the importance of individual agency, choice and decision-making. Students are encouraged to question assumptions and reconcile conflicting ideas and values as they make informed choices in their own lives.